Comparison of conventional and digital radiographic techniques for the assessment of alveolar bone in periodontal disease - Heena Sharma; Parveen Dahiya; Rajan Gupta; Mukesh Kumar; Sunita R Melwani; Lolakshi Kachroo (Wolters Kluwer Medknow Publications, 2019)
Background: Alveolar bone loss at the crest and interdental osseous defects are the frequent outcomes of periodontal disease. Radiographs act as valuable adjunct as they provide essential information regarding the morphology of residual bone and help in determining the prognosis, formulating treatment plan, and establishing the outcome of various therapies. Aims: The aim of the study was to compare the measurements obtained by conventional (intraoral periapical [IOPA] radiographs) and digital radiographs (radiovisiography [RVG]) for the assessment of alveolar bone by utilizing intrasurgical (IS) measurements as the gold standard. Methods: Thirty systemically healthy periodontitis patients with 100 interproximal sites were selected to undergo periodontal flap surgery. IOPA radiographs and RVG were taken before surgery using paralleling cone technique with the help of extension cone paralleling technique (XCP)®. Measurements in case of horizontal and vertical bone loss were taken and compared to IS measurements. Statistical Analysis Used: Analysis of variance and post hoc test were used. Results: No statistically significant difference was found between conventional and digital radiographic method in comparison to IS (IS) method for the assessment of alveolar bone level. Conclusion: Both radiographic methods (conventional and digital) showed statistically nonsignificant results in comparison to IS measurements. Hence, either IOPA radiograph or RVG can be used to visualize the alveolar bone level in periodontal disease.